1994
DOI: 10.1111/j.1365-3164.1994.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response toMicrosporum canisInduced by a Fungal Cell Wall Vaccine*

Abstract: An experimental infection model was used to assess induction of specific immunity against Microsporum canis in cats with an M . canis cell wall vaccine preparation. Kittens 8-9 weeks old (n = 12) received five doses of either vaccine or placebo at biweekly intervals. Specific immunity was monitored via plasma anti-dermatophyte antibody titers and lymphocyte blastogenesis (LB) to dermatophyte antigens. After vaccination, cats were chauenged with viable M . canis spores, and lesion development was monitored. Vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…2,12 Humoral immunity is not considered to be an especially important component of immunity to dermatophytosis, but development of a cell-mediated immune response is paramount. 16 In the study reported here, 2 groups had the mildest infections.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 Humoral immunity is not considered to be an especially important component of immunity to dermatophytosis, but development of a cell-mediated immune response is paramount. 16 In the study reported here, 2 groups had the mildest infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several commercial and experimental vaccines against dermatophytosis have been developed and tested. In some cases there were encouraging results Segal, 1994, 1995;Milan et al, 2004;Westhoff et al, 2010) while in other no protective immunity was found (DeBoer and Moriello, 1994Moriello, , 1995DeBoer et al, 2002). The exception is a vaccine for bovine dermatophytosis (Bovilis ® Ringvac Intervet, the Netherlands).…”
mentioning
confidence: 97%
“…Although it is usually confined to the dead keratinized structures, the infection induces a specific humoral and cellular response [2 -7]. Cellular immune response seems to be associated with clinical recovery [5] and protection against reinfection [8,9]. The role of the humoral response remains unclear.…”
Section: Introductionmentioning
confidence: 99%